Impressive Rate Raise of the Hydrosilation Reaction Through UV‐Activation: Energy and Time Saving. Issue 5 (25th February 2016) - Marchi, Sophie; Sangermano, Marco; Ligorio, Davide; Meier, Patrick; Kornmann, Xavier
Abstract : The curing of silicone polymers can be achieved by the hydrosilation reaction that is usually thermally activated. However, it is observed that the UV‐activated mechanism allows the formation of cured materials in relatively low times leading to a high improvement of energy saving. Moreover, the properties of the two resulting polymers are comparable. Abstract : Silicone materials are widely used in many fields such as electrical or food industries and their consumption is constantly growing. They are generally cured by vulcanization reaction for long time at high temperatures which requires high energy consumption. The possibility to achieve the polymerization of silicone rubbers by UV‐activation promotes the reduction of both time and temperature leading to an impressive energy saving. Indeed, this process is more than 30 times faster than the thermal one. Moreover, the properties of the two resulting materials are comparable, indicating that the low time of UV‐activated hydrosilation reaction is suitable for the formation of crosslinked silicone polymers.